A wild light - Liu, Marjorie M. (Liu, Marjorie M. Hunter Kiss novel., 2010)
For too long Maxine Kiss has felt an inexplicable darkness inside her--a force she channels into hunting the demons bent on destroying the human race. But when she finds herself covered in blood and crouched beside her grandfather's dead body with no memory of what happened, Maxine begins to fear that the darkness has finally consumed her. To keep her sanity, she must embrace the love of the only man who can help her.